RELIGIOUS IDENTITIES AND THE CONTESTING CIVILIZATIONS OF CONTEMPORARY INDIA - Douglas L. Berger & Irfan A. Omar (Journal of Dharma, 2004)
Independent India, after throwing off the yoke of almost a century of British colonial rule, was faced with the dilemma of determining what direction the country would take; what kinds of sacrifices would be required from its citizens; and what sort of political, social and economic transformations would allow this ancient civilization to take its due place among the respectable nation-states of the world. While at least four thousand years of civilizational history were there to draw upon, the sediments of the Indian traditions were both deeply rich and deeply diverse. The challenges of keeping the religious, ethnic, regional, linguistic and social plurality of the Indian heritage alive and vibrant within the new political and geopolitical framework of nationalization and globalisation proved to be fraught with challenges, complexities and conflict. G. J. Larson’s recent work India’s Agony over Religion undertakes a thorough and informed examination of how the pluralism of India’s heritage has affected its varying national identities and contemporary social and political struggles. As the title suggests, this work deals with the religious crisis (or crises) in contemporary India. It seeks to identify a deep connection between modern and ancient strands of thought and culture by way of seeing through the complexity of India’s cultural heritage, the sources of which are as multiple as they are varied. Larson’s argument is that a sustained study of these historical heritages is necessary to see the current crises in a fresh light. He contends that not only are there multiple sources and layers of India’s cultural and intellectual heritage, but that most of these “layers of culture and history are operating in contemporary India ... as present-day living traditions demanding to be heard in the current struggles to shape India’s future”.